The Relationship of Practical Commitment to Religious Beliefs and Psychological Hardiness with Job Burnout Experienced by Teachers in Special Needs Schools of Children in Kerman in 2015 - Mohamadreza Babaei; Masoumeh Sadat Sajjadi; Ghasem Askarizadeh (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: Exceptional education teachers are in a very stressful working environment, which is the cause of burnout. The present study examined the factors affecting job burnout. The purpose of this study was to determine the relationship of practical commitment to religious beliefs and psychological hardiness with burnout among teachers of exceptional children's schools in Kerman, Iran in 2015. Methods: This is a descriptive correlational study. 182 teachers working in exceptional children's schools in Kerman were selected to participate in the study. Data were gathered using a practical commitment to religious beliefs questionnaire, Ahwaz psychological hardiness questionnaire and Maslach burnout inventory questionnaire. The collected data were analyzed using Pearson correlation coefficient. In this study, all the ethical considerations have been observed and no conflict of interest was reported by the authors. Results: The results showed that there was a significantly negative relationship between practical commitment to religious beliefs and psychological hardiness and the burnout of teachers in three dimensions of emotional exhaustion, occupational involvement and depersonalization, but a significantly positive correlation between practical commitment to religious beliefs and psychological hardiness and Teachers' job burnout in the personal performance dimension (P<0.05). Also, the results of multiple linear regression showed that practical commitment to religious beliefs and psychological hardiness of exceptional children teachers could significantly predict job burnout. Conclusion: The results of this study can be used to guide the development and perfection of religious beliefs as well as the inclusion of psychological hardiness components in formal and informal education of teachers of exceptional school children to reduce their vulnerability to stress and control job burnout. For downloading the full-text of this article please click here. Please cite this article as: Babaei MR, Sajjadi MS, Askarizadeh Gh. The Relationship of Practical Commitment to Religious Beliefs and Psychological Hardiness with Job Burnout Experienced by Teachers in Special Needs Schools of Children in Kerman in 2015. Journal of Pizhūhish dar dīn va salāmat. 2020;6(1):47-59. https://doi.org/10.22037/jrrh.v6i1.17908